Edukasi Awal Manfaat Daun Kelor dan Ketumbar bagi Kesehatan Keluarga sebagai Upaya Pemberdayaan PKK Berbasis Herbal Lokal - Sitti Rahbiah; Lilis Nur Hayati; Asdar Djamereng; Mush'ab Al Mubarak; Andi Citra Paraswati; Vikria Vikria (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2025)
INITIAL EDUCATION ON THE HEALTH BENEFITS OF MORINGA AND CORIANDER LEAVES FOR FAMILY WELLNESS AS A COMMUNITY EMPOWERMENT EFFORT THROUGH LOCAL HERBAL UTILIZATION. This community service program aimed to improve health literacy and empower members of the PKK (Family Welfare Movement) through early education on the benefits of moringa (Moringa oleifera) and coriander (Coriandrum sativum) as local herbal ingredients with the potential to support family health. The activity was conducted in Benteng Gantarang Village, Gantarang District, Bulukumba Regency, involving 30 participants. The methods included socialization, health education sessions, hands-on training, and evaluation using a 15-item pre-test and post-test questionnaire. The results revealed a significant increase in participants' understanding, with pre-test scores rising from 46.84% to 80.52% in the post-test. This improvement indicates that the multidisciplinary, participatory-educational approach—integrating agricultural, economic, and information technology perspectives—was effective in raising awareness of the use of local herbal resources. These findings support the need to advance the program toward entrepreneurial development through herbal capsule production, product legalization (PIRT), and digital marketing strategies to broaden the social and economic impact of this community service initiative.